Customer Satisfaction on Yamaha Bike and Scooter in Nepal - Yadav , Aman Kumar; Bista, Nar Bahadur (Nepalese Journal of Business, 2025)
This study examines the customer satisfaction on Yamaha bike and scooter in Nepal. Customer satisfaction is the dependent variable. The selected independent variables are repair and maintenance, spare part supply, services camp, mileage, and price. The primary source of data is used to assess the opinions of respondents regarding repair and maintenance, spare part supply, services camp, mileage, price, and customer satisfaction. The study is based on primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of consumer satisfaction on Yamaha bike and scooter in Nepal. The study showed a positive impact of repair and maintenance on customer satisfaction. It indicates that repair and maintenance service leads to increase in customer satisfaction. Similarly, the study showed a positive impact of spare part supply on customer satisfaction. It indicates that easily available of spare part supply leads to an increase in customer satisfaction. Likewise, the study also revealed a positive impact of services camp on customer satisfaction. It indicates that provision of services camp leads to an increase in customer satisfaction. Further, the study observed a positive impact of mileage on customer satisfaction. It indicates that higher the mileage, higher would be the customer satisfaction. In addition, the study observed a positive impact of price on customer satisfaction. It indicates that affordable price leads to an increase in customer satisfaction.